Penilaian tingkat kontribusi teknologi pada Perusahaan jasa menggunakan model teknometrik - Ida Giyanti (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2015)
This research aims to assess technology contribution level at service company running in the modern management based on information technology. Technometric model developed by UNESCAP was used to evaluate the contribution of the technology component consist of technoware, humanware, infoware, and orgaware. This evaluation yields technology contribution coefficient (TCC) value. Based on the analysis of data,it is known that company TCC value is 0,619. It can be infered that the technological level of the company is semi- modern. Technology component evaluation result shows that contribution of humanware was the highest (H=0,87) among others. The next contribution ranking were technoware (T=0,69), infoware (I=0,38), and orgaware (O=0,26) respectively. Humanware also got the highest valueof technology contribution intensity with the value Bh =0,488 . The next technology contribution intensity value were technoware ( Bt =0,206 ) and infoware ( Bi =0,208 ) which valued the same. The lowest technology contribution intensity value was orgaware ( Bo =0,098 ). Based on this technology assessment, it is suggested that, in short term, the company should focus their resources to strengthen the capability of technoware and infoware. While in long term, control attention of thecompany can be focused on orgaware.